On semigroups of order-preserving transformations of countable linearly ordered sets - Doroshenko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We consider semigroups of endomorphisms of linearly ordered sets ℕ and ℤ and their subsemigroups of cofinite endomorphisms. We study the Green relations, groups of automorphisms, conjugacy, centralizers of elements, growth, and free subsemigroups in these subgroups.